2020
DOI: 10.1101/2020.06.24.169748
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering the regulatory logic of aDrosophilaenhancer through systematic sequence mutagenesis and quantitative image analysis

Abstract: Transcriptional enhancers are short DNA sequences controlling the spatial activity, timing and levels of eukaryotic gene transcription. Their quantitative transcriptional output is thought to result from the number and organization of transcription factor binding sites (TFBSs). Yet, how the various aspects of regulatory information are encoded in enhancer sequences remains elusive. We addressed this question by quantifying the spatial activity of the yellow spot enhancer active in developing Drosophila wings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 70 publications
4
4
0
Order By: Relevance
“…As the effect on the wing blade activity is not observed in D2 block4 , which also randomizes site spot 196 [6] , it is likely that sites for repressors acting on both activities are located within the 100 bp randomized in D2 block4 . In our separate dissection of spot 196 ( 28 ), we reached a similar conclusion for the role of spot 196 [6] . Even without knowing the molecular mechanism at work, our results suggest that spot 196 [6] could be the target site of a global, permissive activator of both activities in the context of segment spot 196 .…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…As the effect on the wing blade activity is not observed in D2 block4 , which also randomizes site spot 196 [6] , it is likely that sites for repressors acting on both activities are located within the 100 bp randomized in D2 block4 . In our separate dissection of spot 196 ( 28 ), we reached a similar conclusion for the role of spot 196 [6] . Even without knowing the molecular mechanism at work, our results suggest that spot 196 [6] could be the target site of a global, permissive activator of both activities in the context of segment spot 196 .…”
Section: Resultssupporting
confidence: 59%
“…3 ). In a recent and independent dissection of spot 196 , we identified a potential site for one or more unknown transcription factor(s), spot 196 [6] , whose mutation (12 bp) nearly abolishes spot 196 activity completely ( 28 ). It is conceivable that these sites necessary for the spot activity also influence the wing blade activity, thereby producing pleiotropic effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A ). Together, these results are consistent with the previous finding that enhancers encode dense spatial information (Fuqua et al 2020; Le Poul et al 2020; Galupa et al 2023).…”
Section: Resultssupporting
confidence: 93%
“…We found that all ten lines had reduced number of nuclei expressing lacZ [ Fig. 2A-C, Fig S2 , also see (Fuqua et al 2020; Galupa et al 2022) for complete analysis of the E3N library], consistent with the previous finding that enhancers encode dense spatial information (Fuqua et al 2020; Le Poul et al 2020; Galupa et al 2022). Seven of them also showed reduced level of expression (FDR-adjusted p < 0.05, Wilcoxon test, Fig.…”
Section: Resultssupporting
confidence: 89%